Loss of C-5 Sterol Desaturase Activity in Candida albicans: Azole Resistance or Merely Trailing Growth? - Luna-Tapia, Arturo (Antimicrob Agents Chemother, 2018)
Increased expression of drug efflux pumps and changes in the target enzyme Erg11p are known to contribute to azole resistance in Candida albicans, one of the most prevalent fungal pathogens. Mutations that inactivate ERG3, which encodes sterol Δ(5,6)-desaturase, also confer in vitro azole resistance. However, it is unclear whether the loss of Erg3p activity is sufficient to confer resistance within the mammalian host, and relatively few erg3 mutants have been reported among azole-resistant clinical isolates. Trailing growth (residual growth in the presence of the azoles) is a phenotype observed with many C. albicans isolates and, in its extreme form, can be mistaken for resistance. The purpose of this study was to determine whether the growth of Erg3p-deficient C. albicans mutants in the presence of the azoles possesses the characteristics of azole resistance or of an exaggerated form of trailing growth. Our results demonstrate that, similar to trailing isolates, the capacity of an erg3Δ/Δ mutant to endure the consequences of azole exposure is at least partly dependent on both temperature and pH. This contrasts with true azole resistance that results from enhanced drug efflux and/or changes in the target enzyme. The erg3Δ/Δ mutant and trailing isolates also appear to sustain significant membrane damage upon azole treatment, further distinguishing them from resistant isolates. However, the insensitivity of the erg3Δ/Δ mutant to azoles is unaffected by the calcineurin inhibitor cyclosporin A, distinguishing it from trailing isolates. In conclusion, the erg3 mutant phenotype is qualitatively and quantitatively distinct from both azole resistance and trailing growth.